Analysis of nickel oxide as a counter electrode for dye-sensitized solar cells using OghmaNano software - Senin, Nur Afiqah Hani; Rummaja, Iskandar Dzukarnain; Idris, Muhammad Idzdihar; Napiah, Zul Atfyi Fauzan Mohammed; Ramlee, Radi Husin; Rashid, Marzaini; Bradley, Luke (Institute of Advanced Engineering and Science, 2024)
Dye-sensitized solar cells (DSSCs), a promising green technology, convert solar energy into electricity more cost-effectively than traditional solar cells. While platinum (Pt) is commonly used in DSSCs, its high cost and toxicity limit practical applications. Recent research aims to develop low-cost counter electrodes with high efficiency. Nickel oxide (NiO), a p-type semiconductor with a wide bandgap, good transmittance, and suitable work function, emerges as a potential alternative for counter electrode of DSSCs. In this work, DSSCs with NiO of thicknesses varying from 100 nm to 1000 nm were simulated to determine its influence on photovoltaic performance using OghmaNano software. The structure of simulated solar cells consists of NiO as counter electrode, zinc oxide (ZnO) as photoanode, N719 as dyes, electrolyte as charge carrier transport, and fluorine-doped tin oxide (FTO) as a contact layer. There are five data of NiO used as an active layer. From the simulation results, NiO-doped gold exhibits the highest power conversion efficiency (PCE) of 15.95% at a thickness of 700 nm, while pure NiO shows the lowest PCE with 4.53% at a thickness of 600 nm. These results have demonstrated that NiO can replace Pt as a counter electrode for DSSCs and doping plays a vital role in increasing efficiency.